2012
DOI: 10.1016/j.susc.2011.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two different carbon nanotube-based surfaces with respect to potassium ferricyanide electrochemistry

Abstract: This paper describes the electrochemical investigation of two multi-walled carbon nanotube-based electrodes using potassium ferricyanide as a benchmark redox system. Carbon nanotubes were fabricated by chemical vapor deposition on silicon wafer with camphor and ferrocene as precursors. Vertically-aligned as well as islands of horizontally-randomly-oriented carbon nanotubes were obtained by varying the growth parameters. Cyclic voltammetry was the employed method for this electrochemical study. Vertical nanotub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 23 publications
2
41
0
Order By: Relevance
“…And these articles show a minute amount of advancement. For example, the sensitivity varied only from 62.8 ± 0.3 to 71.5 ± 0.3 A/mM × cm 2 in case of differently oriented MWCNT [33], while Cottrell effect results in 9 times larger sensitivity by varying the MWCNT orientation on hydrogen peroxide [63]. It is worth noting that these lastmentioned experiments on ferricyanide have been conducted on MWCNT directly grown on silicon substrates while it is hard to find literature on ferricyanide detection done by using MWCNT dropcasted on SPE.…”
Section: Cottrell Effectmentioning
confidence: 95%
See 2 more Smart Citations
“…And these articles show a minute amount of advancement. For example, the sensitivity varied only from 62.8 ± 0.3 to 71.5 ± 0.3 A/mM × cm 2 in case of differently oriented MWCNT [33], while Cottrell effect results in 9 times larger sensitivity by varying the MWCNT orientation on hydrogen peroxide [63]. It is worth noting that these lastmentioned experiments on ferricyanide have been conducted on MWCNT directly grown on silicon substrates while it is hard to find literature on ferricyanide detection done by using MWCNT dropcasted on SPE.…”
Section: Cottrell Effectmentioning
confidence: 95%
“…Among several different approaches for depositing carbon nanotubes, which also include microspotting [53], electrodeposition [54] and the direct growth [33,55], we simply used the drop casting [44]. While microspotting, electrodeposition and direct growth enable a more precise localization of CNT on the working electrode, it has been shown that drop casting may further extend the electro-active area by creating a sort of conducting CNT forest in the insulating area surrounding the WE [56].…”
Section: Sensitivity and Detection Limit With Carbon Nanotubesmentioning
confidence: 99%
See 1 more Smart Citation
“…Two of the most common orientations of CNTs are displayed schematically in Figure 3. In general, films of vertically oriented carbon nanotubes exhibit much better electrical and capacitance properties in comparison to films formed from randomly oriented nanotubes [6,50,[54][55][56][57]. Figure 4 shows the structure of the SWCNT layer formed under CVD growth procedure.…”
Section: Capacitance Properties Of Single-and Multi-walled Carbon Nanmentioning
confidence: 99%
“…This single electron, perfectly reversible process has been well characterized and extensively used in electrochemical studies [101][102][103]. While many of the salts complexed by cyanide are highly toxic, the ferro-and ferri-cyanide forms have greatly reduced toxicity since the iron form tends to not release free cyanide.…”
Section: Model Analytesmentioning
confidence: 99%